Hypothenar Hammer Syndrome: Long-Term Results After Vascular Reconstruction. Issue 1 (January 2016) - Kitzinger, Hugo B.; van Schoonhoven, Joerg; Schmitt, Rainer; Hacker, Stefan; Karle, Birgit
Abstract : Background: Hypothenar hammer syndrome is a rare vascular lesion of the distal ulnar artery in Guyon tunnel caused by acute or repetitive blunt trauma to the hypothenar eminence. Described treatment options vary greatly, from nonoperative management treatments to surgical interventions. The aim of this study was to evaluate the long-term outcomes of patients after surgical reconstruction of the ulnar artery. Methods: In this retrospective study, the results of 12 patients treated for hypothenar hammer syndrome were evaluated. Preoperative and postoperative examinations of the hand were recorded. Function impairment was assessed with the "Disabilites of the Arm, Shoulder and Hand" questionnaire. Comparisons were also made based on ulnar artery patency versus occlusion. All patients were evaluated for ulnar artery patency as determined by Allen's test and magnetic resonance angiography. Results: All patients were men with an average age of 42.8 years. In 3 patients, a direct end-to-end anastomosis of the ulnar artery was performed, and 9 patients received a reconstruction with a reverse interpositional vein graft. Nine vascular reconstructions remained patent after a mean follow-up period of 56.9 months. These patients had a complete or at least partial relief of their pain, dysesthesia, and cold intolerance compared with preoperatively. Patients with reoccluded ulnar arteries were statistically significant younger ( P = 0.036) than patients with patent ulnar artery. They also had a higher pain level ( P = 0.009) and a longer follow-up period ( P = 0.036) than those with patent reconstruction. There was a trend for higher functional impairment in patients with reoccluded ulnar artery ( P = 0.100). Smoking habits showed no influence on ulnar artery patency. Conclusions: For patients with symptomatic hypothenar hammer syndrome and failed nonoperative treatment, surgical intervention is a good option. After more than 4.5 years after surgery 9 of 12 vascular reconstructions remained patent (75% patency rate), ensuring an immediate and long-term improvement of symptoms.